Association between democratic governance and excess mortality during the COVID-19 pandemic: an observational study. Issue 10 (29th June 2022) - Jain, Vageesh; Clarke, Jonathan; Beaney, Thomas
Abstract : Background: Excess mortality has been used to assess the overall health impact of COVID-19 across countries. Democracies aim to build trust in government and enable checks and balances on decision making, which may be useful in a pandemic. But during the pandemic, they have been criticised as being hesitant to enforce restrictive public health measures. Methods: Through linking open-access datasets we constructed univariable and multivariable linear regression models investigating the association between country V-Dem Liberal Democracy Indices (LDI), representing strength of democratic governance and excess mortality rates, from January 2020 to September 2021. We adjusted for several important confounders and conducted a range of sensitivity analyses to assess the robustness of our findings. Results: Across 78 countries, 4.19 million deaths million excess deaths were recorded. On multivariable regression, a one-point increase in V-Dem LDI was associated with a decrease in excess mortality of 2.18 per 100 000 (p=0.004), after accounting for age, gender, wealth and universal health coverage. This association was only partially attenuated by COVID-19 vaccination rates and remained robust in all sensitivity analyses. Conclusions: Democratic governance may have played an important role in mitigating the overall health impact of COVID-19 across countries. This study strengthens the case to broaden the scope of traditional pandemic risk assessment and discussions on preparedness.